Role of Oxidative Stress and Neuroinflammation in Attention-Deficit/Hyperactivity Disorder - Juan Carlos Corona (Antioxidants, 2020)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental disorder of childhood. Although abnormalities in several brain regions and disturbances of the catecholaminergic pathway have been demonstrated, the pathophysiology of ADHD is not completely understood, but as a multifactorial disorder, has been associated with an increase in oxidative stress and neuroinflammation. This review presents an overview of factors that increase oxidative stress and neuroinflammation. The imbalance between oxidants and antioxidants and also the treatment with medications are two factors that can increase oxidative damage, whereas the comorbidity between ADHD and inflammatory disorders, altered immune response, genetic and environmental associations, and polymorphisms in inflammatory-related genes can increase neuroinflammation. Evidence of an association with these factors has become valuable for research on ADHD. Such evidence opens up new intervention routes for the use of natural products as antioxidants that could have potential as a treatment against oxidative stress and neuroinflammation in ADHD.